Automatic Seed Sowing - Ismayudin, Muhammad Danish Aizam; Nor Azman, Nor Najmi Hakimi; Azman, Nur Amirah Sabrina; Mohamed Nor, Mohd Hadri (Multidisciplinary Applied Research and Innovation, 2025)
Agriculture is one of the industries that has been growing rapidly due to advanced technology. Plant cultivation has been one of the most essential undertakings for ages [1]. Tools that reduce time and effort in agriculture have been developed to increase efficiency of cultivating plants. The most common agricultural machinery used is tractor. However, it is not sustainable due to air pollutants caused by combustion of fuel. Furthermore, the use of tractor is not suitable for small scale farming and most of them manually sow by hand. The Automatic Seed Sowing project offers a cost-efficient and eco-friendly solution for small-scale farmers by utilizing electricity for continuous, effective, and low-impact seed sowing. This approach reduces dependence on human labor and fossil fuels. The main goal is to ensure that seeds are accurately placed in the designated holes during the sowing process. This study involves the development of an electric-powered seed sowing machine tailored for small farming plots of 5 m × 5 m. The machine is specifically designed for sowing spinach in soft organic soil and operates solely on a 12 V battery. The methodology covers various aspects including the creation of a flowchart, testing methods, a Gantt chart, drilling methods, and engineering analysis. Regular maintenance, such as battery replacement and repairs or replacement of damaged parts, is required for the machine. This machine's ability to precisely place seeds in pre-marked holes while eliminating the need for fossil fuels and human labor makes it both cost-effective and environmentally friendly. The study suggests that this technique can boost sustainability and increase agricultural productivity.